INDIVIDUAL PSYCHOLOGICAL FEATURES OF THE LEVELS OF HARDINESS OF THE INDIVIDUALITY - Kyrylenko T. S.; Chanchykov I. K. (International Journal of Innovative Technologies in Social Science, 2020)
The article is devoted to the study of hardiness as a systemic concept and to expand the understanding of the features of individual manifestations of personality vitality. The concept of hardiness, developed by S. Muddy, includes three parameters: inclusion, control, risk-taking. In our study, individual manifestations of the vitality of the individual were identified by the characteristics of willpower, temperament, character traits, emotional sphere and self-esteem. The study is based on the concept of personality as an integral individual V.S. Merlin. In concept personality has certain levels: individual properties, individual mental properties, personal properties and the general level of integral individuality. According to these levels, individual personality traits were selected to determine the manifestations of hardiness. On the basis of cluster and analysis of variance, three levels of vitality are distinguished and individual personality traits are found accordingly. The obtained data allowed to describe the individual features of hardiness personalities: type of temperament, willpower, features of the emotional sphere, self-attitude and the most developed positive character traits.